2016
DOI: 10.1002/bit.26008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cell‐surface display and secretory production of cellulolytic enzymes with Saccharomyces cerevisiae Sed1 signal peptide

Abstract: Recombinant yeast strains displaying aheterologous cellulolytic enzymes on their cell surfaces using a glycosylphosphatidylinositol (GPI) anchoring system are a promising strategy for bioethanol production from lignocellulosic materials. A crucial step for cell wall localization of the enzymes is the intracellular transport of proteins in yeast cells. Therefore, the addition of a highly efficient secretion signal sequence is important to increase the amount of the enzymes on the yeast cell surface. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Towards this end, Sso7dstrep and Sso7dhFc were cloned into pct-CT-F2A with the secretory leader sequence SED1SP 41 placed after the F2A peptide (Fig. 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Towards this end, Sso7dstrep and Sso7dhFc were cloned into pct-CT-F2A with the secretory leader sequence SED1SP 41 placed after the F2A peptide (Fig. 7A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the CBHs, we compared the amounts of BGL and EGL secreted into the culture supernatant by the signal peptide MFα, the native signal sequence, and TFPs for SfBGL1 21 and TrEGL2 27, 28 . For EGL activity analysis, the secretion of EGL by the TFP system was analysed by incubating the cell-free culture supernatants of S. cerevisiae harbouring YGaTFPn-EGL with carboxymethylcellulose (CMC) and determining the amount of the reducing sugars formed.…”
Section: Resultsmentioning
confidence: 99%
“…Inokuma et al [53] showed that the replacement of the anchor domain of α-agglutinin with the anchor domain of Sed1 significantly enhanced the activity of surface-displayed β-glucosidase from Aspergillus aculeatus (BGL) and endoglucanase II from Trichoderma reesei (EGII). Further optimization of the promoter and signal peptide of Sed1 additionally increased the display efficiency of both recombinant enzymes [53,54]. Inokuma et al [54] showed that the signal peptide (SP) sequence derived from the S. cerevisiae SED1 resulted in 1.3-and 1.9-fold higher BGL activity in comparison with BGL activity obtained from the constructs bearing SP from R. oryzae glucoamylase (GLUASP) and S. cerevisiae α-mating pheromone (MFα1SP), respectively.…”
Section: Recombinant Protein Fusion To Other Gpi-anchored Proteinsmentioning
confidence: 99%
“…Further optimization of the promoter and signal peptide of Sed1 additionally increased the display efficiency of both recombinant enzymes [53,54]. Inokuma et al [54] showed that the signal peptide (SP) sequence derived from the S. cerevisiae SED1 resulted in 1.3-and 1.9-fold higher BGL activity in comparison with BGL activity obtained from the constructs bearing SP from R. oryzae glucoamylase (GLUASP) and S. cerevisiae α-mating pheromone (MFα1SP), respectively. Using the Sed1 promoter was also favorable because efficient heterologous protein display was achieved by growth fa or prolonged period without any changes in the carbon source.…”
Section: Recombinant Protein Fusion To Other Gpi-anchored Proteinsmentioning
confidence: 99%